1972
DOI: 10.1007/bf02533123
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐cerebroside interaction: The role of α‐hydroxy fatty acids

Abstract: The esterification of cholesterol by the plasma phosphatidyl choline‐cholesterol acyltransferase reaction was studied by two methods, radioisotopic and colorimetric, in the presence of cerebroside, ceramide, or methyl esters of lignoceric or α‐hydroxy lignoceric acid. The radioisotopic method measures esterification of exogenous labeled cholesterol which must be taken up into the lipoprotein‐bound pool prior to its utilization as a substrate. The colorimetric method measures esterification of endogenous lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1977
1977

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although a small part of the lipid may be directly associated in the membrane with basic protein it is probable that most is involved in lipid-lipid interaction through non-polar forces (Finean, 1953;Finean et al, 1968;Chapman, 1972). It has, for example, in model experiments been shown that there is interaction between cholesterol and cerebroside-containing a-hydroxy fatty acids (Mickel & Hill, 1972). Therefore on digestion of myelin basic protein, release of neutral lipid may be simply due to loss of the acidic lipid available for hydrophobic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although a small part of the lipid may be directly associated in the membrane with basic protein it is probable that most is involved in lipid-lipid interaction through non-polar forces (Finean, 1953;Finean et al, 1968;Chapman, 1972). It has, for example, in model experiments been shown that there is interaction between cholesterol and cerebroside-containing a-hydroxy fatty acids (Mickel & Hill, 1972). Therefore on digestion of myelin basic protein, release of neutral lipid may be simply due to loss of the acidic lipid available for hydrophobic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction likely occurs by way of hydrogen bonding with the hydroxyl group of cholesterol. However, the implication this has for the structure and fluidity of myelin, the only membrane known to possess cerebrosides which contain a-hydroxy fatty acids, remains an open question (Mickel and Hill, 1972).…”
Section: Cholesterol: Location and Functionmentioning
confidence: 99%